VD_FINDINFO HC / 2009 / 44 vom 28. Januar 2009 - VD Tribunal cantonal (2009)
PEINE D'ENSEMBLE, PEINE PRIVATIVE DE LIBERTÉ, RÉVOCATION DU SURSIS | 46 al. 1 CP, 46 al. 2 CP, 47 CP, 411 let. h CPP, 411 let. i CPP